Validity of Gotland Male Depression Scale for male depression in a community study: The Sudurnesjamenn study - Sigurdsson, Bjarni; Palsson, Sigurdur Pall; Aevarsson, Olafur; Olafsdottir, Maria; Johannsson, Magnus (Journal of Affective Disorders, 2015)
To access publisher's full text version of this article click on the hyperlink at the bottom of the page Background: Several studies suggest a "male depressive syndrome", where not only the standard symptoms of major depressive disorder (MDD) but also symptoms of anxiety, anger, irritability and antisocial behaviour are prominent. Method: In a community study, 534 males were screened for possible depression by the Gotland Male Depression Scale (GMDS) and Beck's Depression Inventory (BDI). For comparison psychiatrists examined a sub-sample of healthy and depressive males (n=137). The validity of the GMDS was compared both with the BDl and MDD diagnosis according to DSM4V. Results: GMDS was as good as BDl for screening males. ROC-curve analysis gave AUC 0.945 (95% Cl 0.923-0.968) for GMDS when tested against BM. Second, when both scales were tested by ROC-curves against DSM4V, the GMDS had AUC=0.861 (95% Cl 0.800-0.921) and BDl had AUC=0.822 (95% CI 0751-0.893). The estimated prevalence was 14-15%. Limitations: Low participation rare (25%) in the screening phase. Conclusion: GMDS is a valid screening tool for detecting male depression (MDD). Furthermore it is a short self-rating scale, easy to use in daily practice to screen for depression. Our results support recent reports of high prevalence of depressions in the community which supports active screening of males in clinical practice Landakot Medical Foundation Icelandic College of Family Physicians Memorial Foundation of Helga Jonsdottir and Sigurlidi Kristjansson (Medical Division)